ADP-Ribosylation of Rab5 by ExoS of Pseudomonas aeruginosa Affects Endocytosis - Barbieri, Alejandro M. (American Society for Microbiology, 2001)
Pseudomonas aeruginosa exoenzyme S (ExoS) is an ADP-ribosyltransferase that modifies low-molecular-weight GTPases. Here we studied the effect of Rab5 ADP-ribosylation by ExoS on its cellular function, i.e., regulation of early endocytic events. Coculture of CHO cells with P. aeruginosa induced a marked decrease in horseradish peroxidase (HRP) uptake compared to noninfected cells, while coculture with a P. aeruginosa mutant strain that fails to produce ExoS did not lead to any change in HRP uptake. Microinjection of recombinant ExoS into Xenopus oocytes induced strong inhibition of basal HRP uptake by oocytes. Moreover, coinjection of recombinant ExoS with Rab5 abolished the typical stimulation of HRP uptake obtained after GTPase microinjection. Cytosols prepared from injected oocytes were used in an endosome-endosome fusion assay. Cytosol from ExoS-microinjected oocytes was ineffective in promoting endosome-endosome fusion. However, in these conditions, the addition of Rab5 to the assay led to fusion recovery. Finally, we found that the interaction of Rab5 with EEA1 was markedly diminished after Rab5 ADP-ribosylation by ExoS.